1992
DOI: 10.1055/s-2007-1003247
|View full text |Cite
|
Sign up to set email alerts
|

TSH Producing Pituitary Tumor:

Abstract: A 50 year old man with hyperthyroidism secondary to inappropriate secretion of TSH is described. On presentation T3 (42.1 nmol/L), T4 (265 nmol/L) and TSH (17.9 mU/L) were all markedly elevated. A diagnosis of a TSH-secreting pituitary tumor was suspected on the basis of a blunted TSH response to TRH and the absence of suppression of TSH by T3 or bromocriptine, but TSH/alpha subunit molar ratios were uncharacteristically less than 1. Nevertheless, the presence of a tumor was confirmed by computed tomography wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Early studies on somatostatin analogs have demonstrated transient suppressive effects on various pituitary hormones a few hours post-administration. Octreotide doses of 50 – 100 mcg have been shown to reduce average GH levels within a few hours in both healthy adults and acromegaly patients ( 14 , 15 ), as well as reduction in TSH within 6 – 10 hours among patients with TSH-secreting pituitary adenomas ( 16 , 17 ). A single dose of [ 177 Lu]Lu-DOTA-TATE contains about 200mcg (10mcg/mL) of the somatostatin analog component (DOTA-TATE) ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on somatostatin analogs have demonstrated transient suppressive effects on various pituitary hormones a few hours post-administration. Octreotide doses of 50 – 100 mcg have been shown to reduce average GH levels within a few hours in both healthy adults and acromegaly patients ( 14 , 15 ), as well as reduction in TSH within 6 – 10 hours among patients with TSH-secreting pituitary adenomas ( 16 , 17 ). A single dose of [ 177 Lu]Lu-DOTA-TATE contains about 200mcg (10mcg/mL) of the somatostatin analog component (DOTA-TATE) ( 18 ).…”
Section: Discussionmentioning
confidence: 99%